2005
DOI: 10.1128/jvi.79.7.4514-4518.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Antiviral Action of 1-β- d -Arabinofuranosylcytosine on Borna Disease Virus

Abstract: Borna disease virus (BDV) is a nonsegmented, negative-stranded RNA virus that causes neurological diseases in a variety of warm-blooded animal species. Recently, we showed that the nucleoside analog 1-␤-D-arabinofuranosylcytosine (Ara-C) was a potent inhibitor of BDV. This finding was surprising for an RNA virus, since Ara-C is a DNA polymerase inhibitor. Thus, we sought to better define the mechanism of action of Ara-C on BDV. Here, we show that (i) this effect is specific for an arabinoside ring carrying a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…As BDV is able to infect a wide variety of cell types in vitro, even those of nonneuronal origin, we next asked whether this histone acetylation decrease was also observed in other cell types. To this end, histone acetylation levels were evaluated in Vero cells persistently infected by BDV (Vero-BV [24]). We observed that histone acetylation levels were also decreased in Vero-BV cells and that, remarkably, the histone acetylation occurred on exactly the same lysine residues as in the primary neuronal cultures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As BDV is able to infect a wide variety of cell types in vitro, even those of nonneuronal origin, we next asked whether this histone acetylation decrease was also observed in other cell types. To this end, histone acetylation levels were evaluated in Vero cells persistently infected by BDV (Vero-BV [24]). We observed that histone acetylation levels were also decreased in Vero-BV cells and that, remarkably, the histone acetylation occurred on exactly the same lysine residues as in the primary neuronal cultures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, its use is compromised by side effects. Some other antivirals have also been developed against BDV, but these trials have so far remained in the initial phase (Planz et al, 2001;Bajramovic et al, 2004;Volmer et al, 2005;Qian et al, 2010).…”
Section: Treatment and Prevention Of Bdmentioning
confidence: 99%